Estimated Cumulative Incidence of Wisdom Tooth Extractions in Privately Insured US Patients - Schroeder, Alan R.; Newman, Thomas B.; Girod, Sabine; Hashemi, Sepehr; Häberle, Astrid D. (Frontiers in Dental Medicine, 2022)
Objective: To determine the cumulative incidence and predictors of third molar (3M, “wisdom teeth”) extractions in the US. Methods: We retrospectively analyzed a US private dental insurance claims database to create a Kaplan-Meier curve for cumulative incidence of 3M extractions, and used Cox proportional hazards to assess associations between sex, geographic region, and extractions. Results: Between 2007-2016, by age 25, approximately 80% of patients underwent ≥ one tooth and an estimated 50% of patients underwent ≥ one 3M extraction. Factors associated with 3M extractions included female sex (adjusted hazard ratio [aHR] 1.08, 95% CI 1.07 – 1.08) and residence in the West (aHR 1.82, 95% CI 1.81-1.85) or South (aHR 1.5, 95% CI 1.49 – 1.51) geographic regions as compared to the Northeast. Conclusion: 3M extractions are likely the most common surgery performed on US adolescents and young adults. Significant geographic variation suggests that elucidation of the indications for this common procedure is a public health priority.